Complex Projective Synchronization in Drive-Response Stochastic Complex Networks by Impulsive Pinning Control - Xuefei Wu; Zhe Nie (Discrete Dynamics in Nature and Society)
The complex projective synchronization in drive-response stochastic coupled networks with complex-variable systems is considered. The impulsive pinning control scheme is adopted to achieve complex projective synchronization and several simple and practical sufficient conditions are obtained in a general drive-response network. In addition, the adaptive feedback algorithms are proposed to adjust the control strength. Several numerical simulations are provided to show the effectiveness and feasibility of the proposed methods.